ENSURING MACROECONOMIC STABILITY AND INCREASING INVESTMENT ACTIVITY (A case of Uzbekistan) - UGLI, AVAZOV NURIDDIN RUSTAM; TAIROVNA, RAKHMANOVA NAZOKAT; UGLI, KAKHRAMONOV JAKHONGIR BOYMAKHMAT; NURIDDINOVNA, AZIMOVA NILUFAR; NASIROVNA, MURATOVA MUZAYAMKHON (The journal of contemporary issues in business and government, 2021)
This article analyzes the issues of macroeconomic stability and increasing investment activity in Uzbekistan. The article also reviews foreign scientific articles on the subject, as well as local scientific literature and draws scientific conclusions. In addition, the current state of the Uzbekistan’s economy was analyzed and the importance of investment in the economy was determined on the basis of econometric analysis. At the end of the article, based on the findings of the study, scientific conclusions and recommendations were developed to increase macroeconomic stability and investment activity in Uzbekistan.